If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 = 7x + -3 Reorder the terms: 1 + 7x = 7x + -3 Reorder the terms: 1 + 7x = -3 + 7x Add '-7x' to each side of the equation. 1 + 7x + -7x = -3 + 7x + -7x Combine like terms: 7x + -7x = 0 1 + 0 = -3 + 7x + -7x 1 = -3 + 7x + -7x Combine like terms: 7x + -7x = 0 1 = -3 + 0 1 = -3 Solving 1 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 16x^2-28x+7=0 | | 5(x+3)+7x=39 | | (n)4(n)5(n)=50 | | 5.25+2y=5 | | F(x)=8x^3-6 | | 3(u-3)-7u=-1 | | Lg(x)=69-2*lg(10) | | x-7/4=-4 | | 24-y=-5x | | -35=7(w+3)+7w | | 5/3=x/5 | | 50=(n)4(n)5(n) | | x-0.2x=800 | | 8x^3-6y+y^6= | | 3/5=5/x | | -.062*x^2+1.4647*x+5.2405=9 | | 2x^4+x^3+2x=0 | | -.062*x^2+1.4647*x+5.2405=8 | | -.062*x^2+1.4647*x+5.2405=7 | | -.062*x^2+1.4647*x+5.2405=6 | | 4w^2-6w^3-5= | | (x-3)(x*x-2x+1)=0 | | -.062*x^2+1.4647*x+5.2405=5 | | 6x^2-280x+2400=0 | | (12m-11n)-(15m-18n)= | | 9/3(624/8) | | 12u-5u=49 | | 4/5=28/z | | 5(4x-10)=32+18x | | 3/8=12/t | | (2x-14)/(3x-21) | | k/10=27 |